2015
DOI: 10.1002/jor.22845
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tibiofemoral joint contact to net loads at the knee in gait

Abstract: Inverse dynamics analysis is commonly used to estimate the net loads at a joint during human motion. Most lower-limb models of movement represent the knee as a simple hinge joint when calculating muscle forces. This approach is limited because it neglects the contributions from tibiofemoral joint contact forces and may therefore lead to errors in estimated muscle forces. The aim of this study was to quantify the contributions of tibiofemoral joint contact loads to the net knee loads calculated from inverse dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Nevertheless the impact of frontal‐plane stability and co‐activation on muscle forces is not well established. Up to 16% of frontal‐plane stability may be contributed by muscles in varus mal‐aligned individuals, but this is highly variable, with some individuals demonstrating almost no muscular contribution . By applying OA‐type activation patterns, Brandon et al found higher quadriceps forces, yet Adouni et al, who included frontal‐plane internal torques in a geometry‐based contact model with ligaments, did not.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless the impact of frontal‐plane stability and co‐activation on muscle forces is not well established. Up to 16% of frontal‐plane stability may be contributed by muscles in varus mal‐aligned individuals, but this is highly variable, with some individuals demonstrating almost no muscular contribution . By applying OA‐type activation patterns, Brandon et al found higher quadriceps forces, yet Adouni et al, who included frontal‐plane internal torques in a geometry‐based contact model with ligaments, did not.…”
Section: Discussionmentioning
confidence: 99%
“…Medial tibiofemoral contact force (MTFF) is due to a combination of externally applied knee loads [2, 3] and muscles forces [2, 46]. Increased external knee adduction moment (KAM), which is related to increased MTFF [7], has been associated with fast progression of medial knee OA [8], development of chronic knee pain [9], progression of articular tissue pathologies [10], and poor outcomes after high tibial osteotomy surgery [2, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The KAM has been positively correlated with the shape of MTFF during walking [7, 39], but this is not always the case [3, 4, 37, 40]. Studies based on instrumented tibiofemoral prostheses [41] have shown that decreases in the KAM do not necessarily result in decreases to MTFF [37], and that only small changes occurred in the MTFF for gait patterns designed 1to reduce KAM [42].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations